Data from: A multispecies coalescent model for quantitative traits - Mendes, Fabio K.; Fuentes-González, Jesualdo A.; Schraiber, Joshua G.; Hahn, Matthew W. (Dryad, 2018)
We present a multispecies coalescent model for quantitative traits that
allows for evolutionary inferences at micro- and macroevolutionary scales.
A major advantage of this model is its ability to incorporate genealogical
discordance underlying a quantitative trait. We show that discordance
causes a decrease in the expected trait covariance between more closely
related species relative to more distantly related species. If unaccounted
for, this outcome can lead to an overestimation of a trait's
evolutionary rate, to a decrease in its phylogenetic signal, and to errors
when examining shifts in mean trait values. The number of loci controlling
a quantitative trait appears to be irrelevant to all trends reported, and
discordance also affected discrete, threshold traits. Our model and
analyses point to the conditions under which different methods should fare
better or worse, in addition to indicating current and future approaches
that can mitigate the effects of discordance.
Quantitative traits simulated under three-taxon phylogenyR workspace
containing simulated quantitative traits (3
species).5_15_25_50_100loci_rnorm_3spp_w_1ind_ils_1-2-3-4-5_t4.RDataQuantitative traits simulated under five-taxon phylogenyR workspace containing simulated quantitative traits (5 species).5_15_25_50_100loci_rnorm_5spp_w_1ind_ils_1-2-3-4-5_t4.RDataPlottable objectsR workspace containing objects for producing plots.quant_trait_plotting_objs_t4_elife.RData